Study and evaluation of the impacts on the saddle in the L4-L5 and S1 lumbar area during horse riding training session through the use of the last generation inertial sensor - Izzo, R.; Convertini, A.; D'Isanto, T.; Cejudo, A.; Vardei, C. H. (Journal of Human Sport & Exercise, 2020)
The aim of this study is to evaluate the extent of the impact and compression of the spine at the lumbosacral level in equestrian sports. In particular, through the use of inertial sensors (IMU) the impacts on the spine that occur during a training session on horseback will be analysed with specifications currently not present in the literature. Pathologies of the spine account for 5-15% of sports traumatology in horse riding. The study was performed using a K-Track IMU (K-Sport Universal) and the test was carried out by a volunteer, an 18-year-old rider (1.78 mt high, 66.5 kg weight) who participates in competitions, for each of the three horse gaits were performed 15 measurements on 50 meters long track. The data analysis show, that no impact event greater than 1g was detected in the walk, while in the trot as many as 363 events were overrun at an acceleration of 1g and 422 in the gallop. The data collected through IMU, highlighted the need for a partial restructuring of the training plan, which would be more adequate as it would contain a more significant number of specific mobilization and strengthening elements of the spine, for a more adequate building of the muscles involved and to better prevent localized trauma.